OPTIMALISASI OBJEK WISATA MUSEUM TUANKU IMAM BONJOL DAN AIR PANAS RIMBO PANTI DALAM PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN PASAMAN - Redo Pratama Harista; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Optimization of Tuanku Imam Bonjol Museum and Rimbo Panti Hot Spring as Tourism Objects in Increasing Regional Income of Pasaman District. The purpose of this research was keen to investigate the way of optimizing Tuanku Imam Bonjol Museum and Rimbo Panti Hot Spring as tourism objects and the government strategies in optimizing the tourism objects in Pasaman District. The primary and secondary data data were collected through several techniques namely observation, interview, and library research. From the result of the study, it could be inferred that the primary touring destinations in Pasaman District were not fully optimized and the most of the employees found are positioned beyond their competencies.Key Words: Optimization, Tourism Objects, Management, Regional Income (PAD)